Assessment of Entrance Skin Dose in Patients Undergoing Chest and Abdominal Radiography in Selected Hospitals of Dire Dawa, Ethiopia - Simegn, Tigist; Berhanu, Hana; Goshu, Belay Sitotaw (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
The purpose is to evaluate the entrance skin dose (ESD) and establish the diagnostic reference levels (DRLs) for the most common X-ray examinations in adult patients in Dire Dawa City, Ethiopia. Data from 45 adult patients in three selected hospitals were collected between February and July 2022. The patients' ages ranged from 21 to 54 years old, while their heights and weights varied from 150.0 cm to 175.0 cm and 48.0 kg to 75.0 kg, respectively. The study also assessed the mean entrance surface dose (ESD) values for radiography of the chest and abdomen. YMWGH had the lowest mean ESD for abdominal radiography varying from 0.004742 mGy at DCH to 0.010136 mGy at YMWGH. The mean ESD values for chest radiography showed notable diversity, ranging from 0.006277 mGy at SGH to 0.023849 mGy at DCH. Consistency in exposure measurements was indicated by the comparatively minimal ESD standard deviations across all hospitals. These results highlight how crucial it is to optimize mAs settings to lower ESD and enhance radiography procedures. Future studies should examine other factors influencing radiography outcomes and involve a larger spectrum of hospitals. According to, the examination of radiography data from DCH, YMWGH, and SGH, milliampere-seconds (mAs) influence radiographic results in three hospitals in a statistically meaningful way. With extremely low p-values and high t-values, the mAs coefficient is highly significant, highlighting its crucial role in defining image quality and patient safety. This consistent finding across the institutions implies that limiting patient exposure and attaining acceptable radiography results need careful consideration of the mAs settings. The constant term has low t-values and high p-values showing no discernible impact on the results. This is consistent with other research showing that terms frequently make just a little contribution to these kinds of models.